Fabrication of High-Performance rGO/Cu Composites via Arc Induction Melting: A Comprehensive Study on Microstructure, Tribological and Electrical Properties - Macit, Cevher Kursat; Aksakal, Bunyamin; Celik, Umit; Horlu, Merve (Wiley-V C H Verlag Gmbh, 2026)
Reduced graphene oxide (rGO) reinforced copper (Cu) matrix composites were produced using arc induction melting (AIM) to investigate the microstructural, mechanical, tribological, and electrical responses of the system. rGO additions of 0.5 and 1.0 wt% were introduced to clarify interfacial strengthening and functional synergies within the Cu matrix. Characterization through X-ray Diffraction, Scanning Electron Microscopy, Energy-Dispersive X-ray Spectroscopy, Atomic Force Microscopy, and Lateral Force Microscopy confirmed homogeneous rGO dispersion, refined grain structure, and the absence of undesirable secondary phases. Incorporating rGO led to a significant increase in hardness, rising from 65 +/- 4HV30 for pure Cu to 225 +/- 3HV30 for the composite containing 1 wt% rGO. This improvement is associated with Hall-Petch strengthening, Orowan looping, and effective interfacial load transfer. Tribological evaluations demonstrated up to 78% reduction in wear rate and more than 60% decrease in friction coefficient, linked to the formation of a stable, self-lubricating carbonaceous tribofilm. SEM/EDX analyses of worn surfaces confirmed the presence of a continuous protective carbon layer. Electrical conductivity showed a slight improvement, maintaining the structural integrity of the Cu-rGO interface. Overall, AIM proved to be a scalable and energy-efficient approach for fabricating dense and multifunctional Cu-rGO nanocomposites suitable for electromechanical and thermal management applications.
Keywords: arc induction melting; copper matrix composite; electrical conductivity; microstructural characterization; tribological properties